Características da pele de Pseudoplatystoma sp submetida ao processo de curtimento : morfologia, resistência físico-mecânica e química - Prado, Marcellie do (2011)
The objective of this study was to evaluate the general characteristics of the skin and leather of Pseudoplatystoma sp through histological analysis, physico-chemical and mechanical. There were used skins of Pseudoplatystoma sp, from Piscicultura Mar e Terra, in Itaporã-MS. In experiment I was made the characterization of skins of Pseuplatystoma sp by morphology, chemical composition, hydroxyproline and resistance testing after tanning process. It was observed the epidermis, dermis and hypodermis. There was found that the skin has, 60.98% of moisture, 33.49% of crude protein, 1.67% of ether extract, 0.21% of ash and 2.72% of hydroxyproline. The leathers have high resistance to traction (27.47 N/mm2), progressive tearing (90.66 N/mm) and elasticity (69.10%). In experiment II, the objective was to evaluate the resistance of leathers of surubim submitted to change steps in the process of tanning, for different times of action of liming, levels of enzymes used in the purge step, tanning with and without chromium salts, different levels of oils used in the grease step and different tanning techniques. The leathers submitted to liming for 1 hour had a higher (78.89 N/mm) resistance to progressive tearing and maximum force (73.50 N) and there was no significant difference in traction and elongation. For purge, the leathers that were submitted to 0.7% for 40 minutes had a higher (43.80 N/mm2) resistance to traction and elasticity (78.06%), and no difference to progressive tearing (96.86 N/mm) was found. For the leathers tanned with and without chromium salts, the leathers with chromium salts showed higher resistance to traction (20.93 N/mm2), elasticity (52.40%) and progressive tearing (69, 97 N/mm), although they are not diferent from leathers without chromium. In the test with levels of oils, leathers not showed significant difference to traction, elongation and progressive tearing with the levels used. In the test of different techniques, leathers of the treatment three used higher force (225.81 N) and showed higher elasticity (71.81%). The leathers of treatment one showed higher (118.59 N/mm) resistance to progressive tearing. In experiment III, the objective was to evaluate the effect of different levels of oils used in the grease step, on the physico-mechanical and chemical properties of the surubim's leathers. Skins were submitted to tanning process and then it was added to each treatment 8%, 10%, 12%, 14% and 16% of oils. The levels of oils did not affect the thickness (0.98 to 0.66 mm) and resistance of leather to traction (17.72 to 29.15 N/mm2) and elongation (64.63% to 84.13%), maximum force applied in this test (142.70 to 217.53 N) and maximum force in progressive tearing (58.10 to 72.80 N).